2011
DOI: 10.1177/1091581810411931
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Recombinant Human Erythropoietin Against Cisplatin-Induced Oxidative Stress and Nephrotoxicity in Rat Kidney

Abstract: Cisplatin (Cisp) is one of the most widely used chemotherapeutic agents for the treatment of several human malignancies. The efficacy of Cisp is dose dependent and at higher doses serious kidney injury may occur. Recombinant human erythropoietin (rhEPO) has recently been shown to exert an important cytoprotective effect in experimental brain injury and ischemic acute renal failure. The aim of the present study was to explore whether rhEPO administration is protective against Cisp-induced oxidative damage and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…To date, preoperative administration of EPO and RIPC are two putative renoprotective interventions that have been studied in animal models and clinical trials. In early rodent (8,19,23,27), porcine (25) and clinical (26) studies, preoperative EPO administration showed promise for reducing aspects of AKI, but further clinical studies have subsequently proved disappointing (7,9). In contrast, a number of F875 RENOPROTECTION BY EPO OR RIPC clinical studies have shown that, after RIPC before surgery, acute injury to organs (either heart, liver, brain, or kidney) was significantly reduced (3,12,14,30), but negative results have also been reported (17,29).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To date, preoperative administration of EPO and RIPC are two putative renoprotective interventions that have been studied in animal models and clinical trials. In early rodent (8,19,23,27), porcine (25) and clinical (26) studies, preoperative EPO administration showed promise for reducing aspects of AKI, but further clinical studies have subsequently proved disappointing (7,9). In contrast, a number of F875 RENOPROTECTION BY EPO OR RIPC clinical studies have shown that, after RIPC before surgery, acute injury to organs (either heart, liver, brain, or kidney) was significantly reduced (3,12,14,30), but negative results have also been reported (17,29).…”
Section: Discussionmentioning
confidence: 82%
“…EPO has been demonstrated to be renoprotective in rodent models of ischemic (23,27)-, sepsis (8)-, nephrotoxin (19)-or cold ischemia-reperfusion-induced (5) AKI. A pilot clinical study reported encouraging preliminary results (26).…”
mentioning
confidence: 99%
“…[3132] Some other studies documented that a single injection of CDDP at doses of 5-10 mg/kg in rats caused a marked reduction in the glomerular filtration rate and increase in serum levels of BUN and Cr; thus, indicating induction of acute kidney injury. [33343536] The weight loss in animals is caused by CDDP-induced gastrointestinal disturbances. [6373839] We observed that KW increased by CDDP, possibly due to tubular damages and changes in glomerular filtration rate,[40] which accumulates water and salt in the kidney tissue.…”
Section: Discussionmentioning
confidence: 99%
“…EPO also can provide protection for renal cells during toxic insults [41,42]. In the liver, EPO has been shown to protect against ischemic-reperfusion injury [43], but excessive over-expression of EPO can lessen the beneficial effects of EPO [44].…”
Section: Epo Structure and Expressionmentioning
confidence: 99%
“…EPO can block the generation of ROS [27], may prevent oxidative stress at high altitudes [144], and is cytoprotective against oxidative stress that is stimulated by tumor necrosis factor-α (TNF-α) [73]. EPO also can limit oxidative stress injury during cisplatinum administration [42,145] and in models of Parkinson’s disease [57]. EPO can preserve cellular integrity in neurons [35,55,82,146,147], vascular cells [25,6873,76,148], and inflammatory cells of the nervous system [37,7779,149] during oxidant stress mediated injury.…”
Section: Epo Oxidative Stress and Apoptosismentioning
confidence: 99%